2019
DOI: 10.3168/jds.2018-15455
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of different selenium supplements on rumen fermentation and apparent nutrient and selenium digestibility of mid-lactation dairy cows

Abstract: The aim of this study was to evaluate the dosedependent effects of a hydroxy-analog of selenomethionine (HMSeBA) on rumen fermentation, apparent nutrient digestibility, and total selenium absorption in mid-lactation dairy cows, and to compare the effects with those of sodium selenite (SS). Fifty mid-lactation dairy cows with similar milk yields, days in milk, and parity were randomly assigned to 1 of 5 treatments according to a randomized complete block design. The cows were fed a basal diet containing 0.06 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
0
35
1
1
Order By: Relevance
“…It was demonstrated that OH-SeMet affected rumen bacteria differently than sodium selenite, resulting in promotion of rumen fermentation (e.g. increasing total volatile fatty acids and the molar proportions of propionate and butyrate but decreasing rumen pH, ammonia content, and the ratio of acetate to propionate), apparent nutrient digestibility and selenium absorption (Wei et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that OH-SeMet affected rumen bacteria differently than sodium selenite, resulting in promotion of rumen fermentation (e.g. increasing total volatile fatty acids and the molar proportions of propionate and butyrate but decreasing rumen pH, ammonia content, and the ratio of acetate to propionate), apparent nutrient digestibility and selenium absorption (Wei et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the larger urea in the blood was the consequence of a combined improved capacity of the liver to synthesize urea and larger re-absorption of urea by the kidney. Data produced in vitro [46] and in vivo [47] demonstrated a positive effect of organic Se supplementation on rumen fermentation in dairy cows. Thus, it is possible that the larger concentration of plasma urea observed in our study was also due to greater production of microbial proteins.…”
Section: Selenium Bioforti Ed Hay Improves Albumin Production By the mentioning
confidence: 97%
“…Shifts in ruminal fermentation after supplementing inorganic Se may be indicative of either a requirement of Se by ruminal microorganisms or an alteration of fermentation by the chemical reduction of Se compounds (selenate to selenite to elemental Se). Nevertheless, changes in VFA and ruminal fermentation have also been reported in dairy cows (Wei et al, 2019) fed 0.3 and 0.5 mg/kg of organic Se (hydroxy-analog of Se-methionine), which may be a response of ruminal microorganisms to the AA analog rather than an effect of Se.…”
Section: Vfa Concentrationmentioning
confidence: 99%
“…Inorganic forms of Se may undergo chemical reduction in the rumen by the action of ruminal microorganisms (Eun et al, 2013), and hence be partially converted to forms of Se with low molecular weight that have not been chemically identified, but are less available to the animal (Weiss, 2005;Suttle, 2010). Moreover, although positive effects of organic forms of Se on ruminal fermentation have been recently reported (Wei et al, 2019), the effects of inorganic Se on ruminal fermentation are not clear (Serra et al, 1994;Kim et al, 1997;Eun et al, 2013). Therefore, there is a critical need to better understand factors that affect ruminal metabolism of Cu and Se and their effects on ruminal fermentation.…”
Section: Introductionmentioning
confidence: 99%